Use of Boundary Distribution to Assess the Duration of a Stochastic Processes in Underground Mines - Napieraj, Aneta; Snopkowski, Ryszard; Sukiennik, Marta (Archives of Mining Sciences, 2025)
The content of the paper involves a method for analyzing stochastic processes using marginal distribution functions. In the introductory section, the scope of the work was defined, the subject of the research was specified, and an example stochastic process was adopted to illustrate the developed method. The procedure for determining conditional distribution functions and marginal distribution functions of the process duration for an undetermined workforce was characterized. The potential applications of the obtained results were described, and final conclusions were formulated.
Keywords: Stochastic process; stochastic simulation boundary distribution function; process analysis; mining process; underground mine